The Relationship Between Physical Fitness and Learning Concentration of Grade VII Students - Muhammad Naufal Faqih Husain; Agus Darmawan (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2026)
This study aimed to determine the level of physical fitness, the level of learning concentration, and the relationship between physical fitness and learning concentration among seventh-grade students of SMP Negeri 1 Semarang. This research employed a quantitative correlational design with a cross-sectional approach. The sample consisted of 62 students selected through cluster random sampling. Physical fitness was measured using the Tes Kebugaran Pelajar Nusantara (TKPN), while learning concentration was assessed using the Grid Concentration Test. Data were analyzed using descriptive statistics, Kolmogorov-Smirnov normality test with Monte Carlo approach, linearity test, and Pearson Product Moment correlation at a significance level of 0.05. The results indicated that both variables were normally distributed and linearly related. The Pearson correlation analysis showed a positive and statistically significant relationship between physical fitness and learning concentration (r = 0.274, p = 0.031). The coefficient of determination (r² = 0.075) revealed that physical fitness contributed 7.5% to students learning concentration. In conclusion, physical fitness has a positive but low significant relationship with students learning concentration.